Discursive representation of the EU in Brexit-related British media - Alkhammash, Reem (Penerbit Universiti Kebangsaan Malaysia, 2020)
Coverage of the Brexit referendum dominated UK media in the summer of 2016. Previous research has focused on the Leave-leaning press and the representations of politicians within that debate. Analysing the British media representation of the EU is paramount in understanding dominant, conflicting discourses regarding the decision of British voters in the period preceding the referendum. This study compares language use in conflicting discourses of Brexit in British media by adopting a corpus-based discourse analysis using the Brexit corpus in Sketch Engine. Drawing on two corpus methods, namely concordance analysis and collocation analysis of the lexis under study (i.e., the term ‘EU’), results of the analysis show that in the Leave campaign, the EU is represented in a negative sense in that continuing to be a member of the EU is viewed as bringing certain economic danger to the future of the UK and as increasing the prospect of terrorist attacks. However, the EU is represented in the Remain campaign both positively and negatively. It is represented positively in that the British public is reminded that the UK shares similar values to those held by the EU and negatively in that the media are critical of the EU in its current form. The Remain campaign also dismantles narratives made by the Leave campaign detailing the benefits of exit to British sovereignty and economy. This article concludes with a discussion of the dominant discourses about the EU found in the British media.